After January: Kazakhstan's Journey Through Identity and Geopolitics - Ibadildin, Nygmet. author. aut Link
V, 101 p.
Keywords: This book examines Kazakhstan's evolving identity and geopolitical positioning following the January 2022 protests and the Russia-Ukraine conflict. Tracing Kazakhstan’s complex ties with Russia from Tsarist colonization to Soviet legacies, we analyze how national memory, economic governance, and foreign policy are shaped by postcolonial dynamics. The “social contract” under Nazarbayev and Tokayev emphasized stability over reform, but recent crises have forced recalibration. Using postcolonial theory, we explore Kazakhstan’s diplomatic balancing act between Russia, the West, and emerging Turkic alliances. From the trauma of the Asharshylyk famine to reforms after Qandy Qantar, this book offers a comprehensive account of Kazakhstan’s redefined identity, growing regional assertiveness, and the long shadow of empire in its domestic and foreign policy choices. Nygmet Ibadildin is Assistant Professor of Political Science at KIMEP University. He earned his PhD from the University of Tampere and previously worked in journalism, including as editor-in-chief of Energy of Kazakhstan. His research focuses on post-Soviet institutional development, resource politics, and authoritarian resilience. Dinara Pisareva is Assistant Professor at Nazarbayev University. She holds a PhD from the Australian National University. Her research investigates citizen-state relations in authoritarian regimes, especially during crises. She is currently studying public responses to the January 2022 events and state-led narratives in Kazakhstan. Nurmakhan Tastaibek holds an MA from Nazarbayev University. His research examines authoritarian governance, public opinion, and identity in Central Asia. He co-authored a chapter on state framing of the January 2022 unrest and is conducting research on LGBTQI+ attitudes in Kazakhstan.